2018
DOI: 10.1186/s40880-018-0290-3
|View full text |Cite
|
Sign up to set email alerts
|

Aldolase A promotes proliferation and G1/S transition via the EGFR/MAPK pathway in non‐small cell lung cancer

Abstract: BackgroundOur previous study demonstrated that aldolase A (ALDOA) is overexpressed in clinical human lung squamous cell carcinoma and that ALDOA promotes epithelial–mesenchymal transition and tumorigenesis. The present study aimed to explore the function of ALDOA in the modulation of non-small cell lung cancer (NSCLC) proliferation and cell cycle progression and the potential mechanism.MethodsALDOA was knocked down by short hairpin RNA in H520 and H1299 cells. ALDOA was overexpressed with vectors carrying the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 81 publications
2
50
2
Order By: Relevance
“…ALDOA is much more abundant in the cytoplasm and we also found no clear relationship between cell body ALDOA levels and cell proliferation status. Nuclear ALDOA has been linked to cell proliferation (Mamczur et al 2010(Mamczur et al , 2013Fu et al 2018). While we were able to detect nuclear ALDOA we found no clear relationship between ALDOA protein levels and cell proliferation status.…”
Section: Aldoacontrasting
confidence: 74%
See 2 more Smart Citations
“…ALDOA is much more abundant in the cytoplasm and we also found no clear relationship between cell body ALDOA levels and cell proliferation status. Nuclear ALDOA has been linked to cell proliferation (Mamczur et al 2010(Mamczur et al , 2013Fu et al 2018). While we were able to detect nuclear ALDOA we found no clear relationship between ALDOA protein levels and cell proliferation status.…”
Section: Aldoacontrasting
confidence: 74%
“…The metabolic role of cytoplasmic ALDOA is well established, and ALDOA also has other non-glycolytic "moonlighting" roles such as regulating mitochondrial function and cyctoskeleton stability (Orosz et al 1988;Pagliaro and Taylor 1992;Kao et al 1999;Jewett and Sibley 2003;Buscaglia et al 2006). In addition to its cytoplasmic roles, ALDOA has been observed in the nucleus (Mamczur and Dzugaj 2008;Mamczur et al 2010Mamczur et al , 2013 where it has been suggested to impact cell cycle by positively regulating cyclin D1 expression to mediate 30 G1/S progression (Ritterson Lew and Tolan 2012;Fu et al 2018). Cell-culture studies show ALDOA sub-cellular localisation depends on the availability of energetic substrates, with addition of glucose driving ALDOA protein to the cytoplasm (Mamczur et al 2013).…”
Section: Aldoamentioning
confidence: 99%
See 1 more Smart Citation
“…Aldolase converts fructose 1-6, bisphosphate to glyceraldehyde 3-phosphate (G3P) and Dihydroxyacetone phosphate (DHAP), so they control fatty acid synthesis and glycolysis to further affect the Warburg effect or oxidative phosphorylation (OXPHOs). Otherwise, overexpression of ALDOA has been proven to be associated with poor overall outcome in colorectal and prostatic cancers, as well as lung non-small cell carcinoma [8,9,10]. ALDOA has a hypoxia response element (HRE) in the promoter region.…”
Section: Introductionmentioning
confidence: 99%
“…MAPK inhibitors, particularly JNK, enhance the cell death effects in H 2 O 2 -treated lung cancer cells by increasing superoxide anion and glutathione depletion [35]. The EGFR/MAPK pathway mediates aldolase A-promoted cyclin D1 expression and proliferation and G1/S transition in NSCLC [36]. Activation of the MAPK pathway by the long noncoding RNA TUC338 promotes the invasion of lung cancer [37].…”
Section: Discussionmentioning
confidence: 99%